2002
DOI: 10.1063/1.1464538
|View full text |Cite
|
Sign up to set email alerts
|

Segmental dynamics in a blend of alkanes: Nuclear magnetic resonance experiments and molecular dynamics simulation

Abstract: The segmental dynamics of a model miscible blend, C 24 H 50 and C 6 D 14 , were investigated as a function of temperature and composition. The segmental dynamics of the C 24 H 50 component were measured with 13 C nuclear magnetic resonance T 1 and nuclear Overhauser effect measurements, while 2 H T 1 measurements were utilized for the C 6 D 14 component. Use of low molecular weight alkanes provides a monodisperse system in both components and allows differentiation of dynamics near the chain ends. From these m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 35 publications
1
16
0
Order By: Relevance
“…The corresponding dimethylnaphthalene relaxation times increased in the model asphalt systems: c = 1050 ps in the asphaltene2-based system and c = 1930 ps in the asphaltene1-based system. Budzien et al 29 found similar changes in relaxation time for C 6 and C 24 alkanes. The reason is that for a molecule placed in a more viscous solvent, its dynamics are slowed down by bigger surrounding molecules.…”
Section: Relaxation Time In Model Asphaltssupporting
confidence: 50%
See 3 more Smart Citations
“…The corresponding dimethylnaphthalene relaxation times increased in the model asphalt systems: c = 1050 ps in the asphaltene2-based system and c = 1930 ps in the asphaltene1-based system. Budzien et al 29 found similar changes in relaxation time for C 6 and C 24 alkanes. The reason is that for a molecule placed in a more viscous solvent, its dynamics are slowed down by bigger surrounding molecules.…”
Section: Relaxation Time In Model Asphaltssupporting
confidence: 50%
“…Similar behaviors ͑ 0 Ͼ KWW ͒ have been reported for other systems. 29 The decrease in ␤ indicates a broader range 194502…”
Section: Relaxation Time Diffusion and Viscosity For Naphthalenementioning
confidence: 99%
See 2 more Smart Citations
“…It appears therefore, in agreement with the report by McDonald and Hanna for a simulation of 8CB with a similar UA FF, but devoid of electrostatic interactions, [25] that tumbling times for nCBs are faster than the ones found for cinnamates, [11] probably because of the higher flexibility and lower molecular weight of the former. It should be also pointed out that, at least for alkanes, UA FFs are known to speed up rotational dynamics [50] and we might expect a somewhat faster dynamics for our UA nCB as well when compared to the fully atomistic case.…”
Section: Calculation Of Orientational Order Parametersmentioning
confidence: 98%